Knowledge & awareness of burn first aid among health-care workers in Saudi Arabia: Are health-care workers in need for an effective educational program? - Hatan Mortada; Nader Malatani; Hattan Aljaaly (Journal of Family Medicine and Primary Care, 2020)
Objective: The objective of this study was to assess the level of awareness and knowledge of first aid for burns among healthcare workers in Saudi Arabia. Methods: We conducted a cross-sectional study between September 2 and December 5, 2019, via a self-administered online questionnaire among healthcare workers at a university hospital. The questionnaire comprised 24 questions divided into two sections pertaining to demographics and first aid for burns. This study was approved by the Research Ethics Committee. Results: We included 1,438 respondents in this study. Females comprised 68.2% (982) of the respondents. A total of 513 respondents (35.7%) were medical students. The mean burn knowledge score of all respondents was 8.07 ± 2.03 out of 13. Interestingly, 940 individuals (65.4%) used traditional medications on the burn area. Knowledge regarding antibiotic use in burn injuries was poor—1,199 (82.3%) study participants agreed that antibiotics are beneficial in the case of burns, which is a wrong act. The mean knowledge score was significantly different across groups of different ages, sexes, nationalities, marital statuses, and job positions (P < 0.001). Conclusion: The level of awareness of first aid for burn patients among healthcare workers was insufficient, and the unnecessary use of traditional medicines and antibiotics in burn patients being high. Moreover, this study confirmed the need for an effective educational program among healthcare workers.